Pengembangan Panduan Mendesain Konten E-Learning pada Platform Totara - Maharani Eka Pratiwi; Kunto Imbar Nursetyo; R.A Murti Kusuma Wirasti (Jurnal Pembelajaran Inovatif, 2018)
The development research aims to produce a guidelines for designing e-learning content in general and spesific in Totara platform. The guides are packed in a printed book and leaflet. This guidelines is meant to be used by lecturer in FIP UNJ. This development research is referring to Rowntree’s model that consists of three major stages; planning; preparation of writing; writing and editing. The evaluation on this development research was conducted through expert review and face-to-face tryouts. The evaluation involving one subject matter expert, one media expert, and three users. The average value obtainded from the expert review by the subject matter expert was 3,6 overall excellent. The average value obtainded from the expert review by the media expert was 3,1 overall good. In face-to-face tryouts, obtained the average score 3,8 which signifies the overall guidance is excellent and can be used to guide lecturer in designing e-learning content, spesifically in Totara platform.